(untitled) (Comprehensive Journal of Science, 2025)
The mucosal barrier, which offers both physical and immunological defense against infections, interacts closely with the gut microbiota in dairy cows, which is essential for digestion, nutrient absorption, and intestinal health maintenance. Theoretical frameworks highlight the importance of a diversified and balanced microbial population, which is dominated by phyla like Bacteroidetes and Firmicutes, in promoting disease resistance and host resilience. Conceptual models illustrate the beneficial connections between microbial balance, mucosal health, and immune function by indicating that optimum microbial diversity is linked to improved intestinal immunity and greater mucosal integrity. These findings highlight how crucial it is to keep the gut microbiota consistent in order to support immunological resilience, avoid dysbiosis, and guarantee successful host–microbe interactions in dairy cows—all of which improve general health and productivity.